2004
DOI: 10.1261/rna.5176604
|View full text |Cite
|
Sign up to set email alerts
|

The kink-turn motif in RNA is dimorphic, and metal ion-dependent

Abstract: The kink-turn (K-turn) is a new motif in RNA structure that was identified by examination of the crystal structures of the ribosome. We examined the structural and dynamic properties of this element in free solution. The K-turn RNA exists in a dynamic equilibrium between a tightly kinked conformation and a more open structure similar to a simple bulge bend. The highly kinked form is stabilized by the noncooperative binding of metal ions, but a significant population of the less-kinked form is present even in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
214
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 149 publications
(244 citation statements)
references
References 39 publications
30
214
0
Order By: Relevance
“…In the absence of protein binding, K-turn RNA exists in an equilibrium between the tightly kinked and a more extended structure, and the position of equilibrium is determined by metal ion concentration. The kinked conformation confers strongly retarded electrophoretic mobility to the RNA, whereas the extended structure migrates with a mobility typical of a simple 3-nt bulge (Goody et al 2003;Matsumura et al 2003). Fluorescence resonance energy transfer (FRET) measurements (Goody et al 2003) show that the RNA undergoes an ion-induced two-state transition between the two structures, consistent with molecular dynamics studies that have predicted structural bistability in K-turn RNA (Cojocaru et al 2005;Razga et al 2005Razga et al , 2006.…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…In the absence of protein binding, K-turn RNA exists in an equilibrium between the tightly kinked and a more extended structure, and the position of equilibrium is determined by metal ion concentration. The kinked conformation confers strongly retarded electrophoretic mobility to the RNA, whereas the extended structure migrates with a mobility typical of a simple 3-nt bulge (Goody et al 2003;Matsumura et al 2003). Fluorescence resonance energy transfer (FRET) measurements (Goody et al 2003) show that the RNA undergoes an ion-induced two-state transition between the two structures, consistent with molecular dynamics studies that have predicted structural bistability in K-turn RNA (Cojocaru et al 2005;Razga et al 2005Razga et al , 2006.…”
Section: Introductionsupporting
confidence: 69%
“…We have previously shown that RNA duplexes containing a central K-turn sequence exhibit strongly retarded electrophoretic mobility in polyacrylamide in the presence of Mg 2+ ions (Goody et al 2003), consistent with the adoption of a highly kinked conformation. Sequence changes that disrupt the canonical K-turn sequence lead to normal electrophoretic mobility for an RNA duplex of the same length interrupted by a 3-nt bulge.…”
Section: Analysis Of Folding By Gel Electrophoresismentioning
confidence: 64%
See 3 more Smart Citations